Exploring EFL students’ receptive in improving their English productive skills: Existing challenges and expective solutions - Aisyah, Sri (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED)DO - 10.18860/icied.v10i1.3595, 2025)
The aim of this research is to identify and assess receptive skills in English Language and Literature among English literature students, and to address the challenges they face in developing these skills. This research focuses on the listening and reading skills of students majoring in English Language and Literature. The methodology used includes exploratory data analysis and quantitative analysis. The findings revealed several important points. First, there is diversity in students' proficiency levels in receptive skills, with the majority at the intermediate level. Second, challenges arise from various factors, including limited exposure to English outside the classroom, lack of motivation, and lack of self- confidence. Proposed solutions include the integration of interactive learning methods and the provision of additional listening and reading classes. The researchers concluded that several actions are needed to further develop the receptive skills of English literature students. Effective teaching strategies include the use of authentic materials such as books and films, activities that allow students to actively participate in the language comprehension process, fostering a collaborative learning environment, expanding language support services, utilizing technology-enhanced learning approaches, and improving pedagogical skills.